tìm `x` biết: `x“.“(x – 2)` `+` `28` `=` `(x + 2)^2` `+` `12`

tìm `x` biết:
`x“.“(x – 2)` `+` `28` `=` `(x + 2)^2` `+` `12`

2 bình luận về “tìm `x` biết: `x“.“(x – 2)` `+` `28` `=` `(x + 2)^2` `+` `12`”

  1. ⇔x(x – 2) + 28 = (x + 2)^2 + 12
    ⇔x^2 – 2x + 28 = x^2 + 4x + 4 + 12
    ⇔x^2 – 2x + 28 = x^2 + 4x + 16
    ⇔x^2 – 2x + 28 = + (x^2 + 4x + 16)
    ⇔x^2 – 2x + 28 – (x^2 + 4x + 16) = 0
    ⇔x^2 – 2x + 28 – x^2 – 4x – 16 = 0
    ⇔(x^2 – x^2) + (-2x – 4x) + (28 – 16) = 0
    ⇔-6x + 12 = 0
    ⇔-6(x – 2) = 0
    ⇔x – 2 = 0
    ⇒ x = 2
    Vậy x = 2
     

    Trả lời
  2. $x(x-2) +28 = ( x+2)^2 + 12 $
    $<=> x(x-2) – (x + 2)^2 +28 -12 = 0 $
    $ <=> x^2 – 2x – ( x^2 + 4x + 4 ) + 16 = 0 $
    $ <=> x^2 – x^2 – 2x – 4x – 4 + 16 = 0 $
    $<=> -6x + 12 = 0 $
    $ <=> -6x = -12 $
    $<=> x = 2$
    $\text{ Vậy x = 2 }$
    $#dangduy34hd$
     

    Trả lời

Viết một bình luận

Câu hỏi mới